Analysis of the mitochondrial CYTB gene sequence in human populations of northeastern Bosnia - Ahmic, Adisa; Mujkic, Irma; Ismailovic, Anel; Halilovic, Emir; Lasic, Lejla; Kalamujic, Belma; Pojskic, Naris (Anthropological Review, 2019)
This study offers the first report on variation sequence of the mitochondrial cytochrome b (MTCYTB) gene in populations from Bosnia (northeastern Bosnia). This study was designed on the analysis of the genetic diversity of two populations of different cultural-anthropological and genetic origin, Roma population and native/non-Roma population. The main aim of our study was to estimate the usefulness of the CYTB sequence in the analysis of genetic categorization of different populations and intergroup diversity, as well as to provide some additional information on haplogroup-associated polymorphisms within the CYTB region in defining haplogroup status. Estimation of the genetic diversity was done using intra and intergroup genetic indices. The population-specific polymorphisms have been found in both categories of the populations. The results of the analysis of genetic differentiation show significant pairwise Fst differences between the Romani and native populations. Also, registered significant genetic differentiation is illustrated on the level of genetic variation between subpopulations of the Roma and non-Roma origin. The important result in our study is the confirmation of the significance of the triad of polymorphisms T14783C-G15043A-G15301A, indicating the influence of Asian component of the maternal gene pool on the genetic structure of the studied population of the Roma. Our data show that the haplogroup polymorphisms exist in the CYTB region and can provide useful information on the haplogroups that were defined only by the control region of the mtDNA. The results of this study indicate the region of CYTB gene can be a benefit in providing some additional information in the analysis of genetic structure of human populations and can be additionally applied in population studies.